Analisa Kualitas Layanan Website Gofeeder Terhadap Kepuasan Mahasiswa STAH Dharma Nusantara Jakarta dengan Metode Webqual - Pramitasari, Fitriyani; Zuraidah, Eva (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Gofeeder website as a means of academic information used in STAH Dharma Nusantara Jakarta, currently the utilization of the website has not been maximally carried out by STAH DNJ students, but has begun to be effective within four years. Obstacles that are often experienced by students have difficulty in logging in to customize the website, payments that are still manual have not been integrated with the Virtual Account and not yet the maximum function of the website service. For this reason, researchers analyzed student satisfaction as users of Gofeeder website services on website quality by using the webqual 4.0 method which focuses on 3 dimensions of webqual 4.0, namely Usability, Information Quality and Interaction Service Quality, to measure user satisfaction. The study used a statement instrument based on webqual dimension 4.0, using questionnaires shared with 65 respondents taken based on simple random sampling from a population of 157 active college students. Data processing uses SPSS version 26. The results of the F test stated that the common influence of 3 dimensions of Usability, Information Quality, Interaction Service Quality on user satisfaction, with a P-Value or significance value of 0.000, meaning a probability value of < 0.05. The result of the test t showed the variable Usability had no significant effect on user satisfaction, with a p-value of 0.405 (probability value > 0.05), the variable that affected was the quality of information (value of information). p-value 0.002), and interaction service quality (p-value 0.000). The results of the determination coefiesien test showed the effect of 3 dimensions of webqual 4.0 on user satisfaction (user satisfaction) of 86.10%, and the remaining 13.90% was influenced by other factors not used in this study